Water Remediation (Energy, Environment, and Sustainability,, 2018)
This book presents the state-of-the-art in the area of water remediation. It covers topics such as decentralized ecological wastewater treatment, applications of remote sensing and geographic information systems (GIS) in water quality monitoring and remediation, water remediation through nanotechnology, and processes used in water purification. The contents of this volume will prove useful to researchers, students, and policy makers alike. .